Examining relationship among self-esteem with obesity, physical fitness level and participation to sport - Emrah Atay; Meric Eraslan; Yılmaz Yuksel (Türk Spor ve Egzersiz Dergisi)
This study' purpose was to examine relationship among self-esteem with obesity, physical fitness level and participation situation to sport. 115 male and 124 female participated to study. Participants' mean age is 12.98±1.04 year, mean height 157.38±9.21 cm, mean BMI value 19.37±3.63 kg/m2. Only %28 of participants participates to sport. Besides, their %73.6 participates to sporting activities out of lesson. Coopersmith Self-Esteem Inventory was used as data collection material at study. Inventory is comprised of 25 items and minimum score to be taken from inventory is 0, maximum score is 25. Vertical jump, handgrip strength, flexibility and plates tapping measurements were taken from participants and these were standardized for determination of physical fitness level. Mann-Whitney U, Kruskal Wallis-H and Spearman Correlation analyzes were applied as statistical analyze method. No statistically significant difference was found between self-esteem levels as participants' gender, doing licensed sport, participation to sporting activities out of lesson and obesity situations (p gt;0.05). Besides, it was established that there was no significant relationship between self-esteem and physical fitness level (p gt;0.05). Self-esteem is a case to be effect a lot of factor. Therefore, factors to be effect self-esteem are standardized at researches to be conduct regarding self-esteem. Thus, relationship among self-esteem with doing sport situation, physical fitness level and obesity situation is may be established correctly.